Rādheśyāma Śarmānī pratinidhi vārtāo - Śarmā, Rādheśyāma (Gujarāta Sāhitya Akādamī, 2004)
Selected stories of a Gujarati author.
Short stories - In Gujarati
Keywords: Gujarātī-Sprache; Kurzgeschichte; Geschichte 1900-2003